2005
DOI: 10.1111/j.1096-3642.2005.00193.x
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenetic transition from unicuspid to multicuspid oral dentition in a teleost fish: Astyanax mexicanus, the Mexican tetra (Ostariophysi: Characidae)

Abstract: Teleost fishes display a remarkable diversity of adult dentitions; this diversity is all the more remarkable in light of the uniformity of first-generation dentitions. Few studies have quantitatively documented the transition between generalized first-generation dentitions and specialized adult dentitions in teleosts. We investigated this transition in the Mexican tetra, Astyanax mexicanus (Characidae), by measuring aspects of the dentition in an ontogenetic series of individuals from embryos to 160 days old, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(71 citation statements)
references
References 57 publications
(73 reference statements)
3
67
1
Order By: Relevance
“…3A). Despite morphology having been largely used as the basis for species descriptions, many species show a high degree of phenotypic plasticity depending on habitat conditions, and the influence of allometry in morphometric measurements has been widely recognized (Hood & Heins, 2000;Trapani et al, 2005). We conclude that morphologic measurements alone are not appropriate diagnostic characters for the identification of Yuriria species.…”
Section: Morphometricsmentioning
confidence: 86%
“…3A). Despite morphology having been largely used as the basis for species descriptions, many species show a high degree of phenotypic plasticity depending on habitat conditions, and the influence of allometry in morphometric measurements has been widely recognized (Hood & Heins, 2000;Trapani et al, 2005). We conclude that morphologic measurements alone are not appropriate diagnostic characters for the identification of Yuriria species.…”
Section: Morphometricsmentioning
confidence: 86%
“…1A). Trapani et al (Trapani et al, 2005) identified the first teeth to appear in larvae as one attached to each premaxillary bone and one on each side of the dentary bone midline (Fig. 1B,C).…”
Section: Resultsmentioning
confidence: 99%
“…The location of developing replacement teeth in ray-finned fishes may be either extraosseous (in the soft tissue outside of the bone to which they attach) or intraosseous (in sockets within the bone) (Trapani, 2001). The zebrafish and other cypriniforms share the ancestral condition of extraosseous replacement tooth formation, with their closest relatives exhibiting intraosseous development occurring within the Characiformes (Trapani, 2001;Trapani et al, 2005).…”
Section: Development Of Replacement Teethmentioning
confidence: 98%